The Audit Committee Characteristics and Earnings Quality: Evidence from Jordan - Allam Mohammed Mousa Hamdan; Sabri Maher Sabri Mushtaha; Abd Almuttaleb Mohammed Al-Sartawi (Australasian Accounting, Business and Finance Journal, 2013)
The aim of the paper is to investigate the relationship between audit committee characteristics and earnings management. Samples in the study included 50 industrial companies listed on the Amman Stock Exchange ASE. Two models were used to measure earnings quality: one which depends on earnings continuity as an indication of quality, and one which depends on the decrease of discretionary accruals of quality, using pooled data regression for the two tests (Ordinary Least Squares OLS and Binary Logit). The study found that there was an influence of some standard characteristics of the audit committee on earnings quality.
Keywords: Audit Committee Characteristics; Earnings Quality; Amman Stock Exchange